Participatory Management of Forests in West Bengal - Palit, S. (Indian Forester, 1991)
In a country like India where resources are limited and demand is high, participatory management is perhaps the only answer in many spheres. The demand-resource imbalance is primarily created by excess population. Here the Idea would be to utilise the population as a resource to bridge the gap between demand and resources. Equity issues get sorted out in the process and the most satisfactory solution in the circumstances in arrived at. The participatory management of forest was thought of as the only option available to save the forests when all conventional methods failed and the administration was suffering from a sense of bankruptcy. Although a beginning was made quite Informally, a great measure of success has been achieved in a short span of time and with minimal investment. The need of the hour is to ensure sustainabliity of the effort and to spread the system to areas which are yet to come under its fold. The historical background, the necessity, the evolutionary process, the organisational aspects and the methodology have been discussed in the paper.